(untitled) (Bangladesh Journal of Agricultural Research, 2015)
Conservation agriculture (CA) based tillage technology permits direct seeding through the moderate level of crop residue. CIMMYT introduced this technology in the farmers field of Bangladesh for wheat crop in collaboration with Wheat Research Centre, Bangladesh Agricultural Research Institute (BARI). Farmers accept CA based tillage technologies considering the advantages of higher yields, reduced cost of tillage operation, and minimum turn around time between the crops. Up land crops are more suitable under these tillage technologies. Weed management in rice cultivation is not yet in a good shape. Most of the tillage implements are operated by imported Chinese two wheel tractor (power tiller). There are few four wheel tractor CA implement using in research farm. Local manufacturers are being fabricated these cost effective small minimum tillage seed drill, raised bed planter, zero till drill, and strip till drills efficiently in different districts of Bangladesh. Farmers accept CA technologies in their field, especially raised bed planting and minimum tillage technology. There are about 425 numbers of raised bed planters and 865 minimum tillage seed drill in the country. Area coverage under bed planting and minimum tillage system are 5764 ha and 21850 ha, respectively. There are 20125 numbers of farmers involved in raised bed farming. There is a big prospect accelerating the CA based tillage technology in the farmers field as irrigation water availability becoming limited or more costly. Mind set up is the big issue for adopting CA tillage technology. Training and multi disciplinary approaches can push forward these tillage technologies ahead. Bangladesh J. Agril. Res. 40(2): 235-248 June 2015